POTENSIALITAS UNSUR KOMUNIKASI SOSIAL DRAMATARI TOPENG BABAD - I Nyoman Putra Adnyana Adnyana; R.M. Pramutomo (Institut Seni Indonesia Surakarta, 2013)
This article originally based on a research’s results in the first years of the drance drama genre inBali called Topeng Babad dance drama performance. In the first year this article tried to concentrateon the Topeng Babad dance drama as a media of social communication amongs both theperformers and the audience either. The urgency of this article focussed on the identificationpropose to the dramatic materials sources of the performance, a choreographycal aspect as aprototype on the performance, and a guiding book based on chooreographycal aspects on thedance drama itself. For this reason this article will examine a descriptive method which is exposeof the basic materials in Topeng babad tradition related to its function to the media of socialcommunication. While this article exploring the descriptive method, one of the important resultswas also related to the action research through the several ways like library review, observation inTopeng Babad dance drama dance style, interview with some informan, and focus group discussionamong experts and artist in the Topeng Babad dance drama.